(untitled) (XXI Century. Spanish Literature and Culture, 2013)
In his novels Travesía de Madrid (1966), El Giocondo (1970) y Sinfonía borbónica (1987) Francisco Umbral offers the reader a story about the world of homosexuals, and challenges the authority of puritanical Spain that deems the homosexual life as improper while hiding behind the Law of Danger and Social Rehabilitation (La Peligrosa, 1958). The writer does not approve of either the beliefs or the homosexual life of pleasure, and portrays a Madrid full of “medusas entre dos aguas” that sinks into the mud of a new Sodom and Gomorrah. To the insatiable linguist that is Umbral, this topic is going to give him the possibility to play all kinds of literary games, and in the process make a lot of enemies. Then, in 1994, through a masterful pirouette, he will change his estrategy, and support the victims and face the executioners. From his position in El Mundo, he will confront the church, the army and José María Aznar’s government. He will expose the politics, economic and social estrategies of a society that has not changed its way of thinking, and whose social problems remain the same; and pose the question: outside the fiefdoms or ghettos of Chueca (Madrid), Gayxample (Barcelona), Sitges or Ibiza, does contemporary Spain really accept homosexuals a priori, or are homosexuals pieces of vulgar economic and political games?